2012
DOI: 10.4103/2153-3539.93399
|View full text |Cite
|
Sign up to set email alerts
|

Virtual microscopy using whole-slide imaging as an enabler for teledermatopathology: A paired consultant validation study

Abstract: Background:There is a need for telemedicine, particularly in countries with large geographical areas and widely scattered low-density communities as is the case of the Canadian system, particularly if equality of care is to be achieved or the difference gap is to be narrowed between urban centers and more peripheral communities.Aims:1. To validate teledermatopathology as a diagnostic tool in under-serviced areas; 2. To test its utilization in inflammatory and melanocytic lesions; 3. To compare the impact of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 9 publications
2
49
0
1
Order By: Relevance
“…Massone et al 20 reported, in 2007, significant problems with a WSI system for inflammatory cases; they noted that further system and technology development and additional training might improve accuracy. In 2012, Al Habeeb et al 15 reported concordance rates of 96% (76 of 79) and 100% (12 of 12) in a multiple-armed study, and they concluded modern WSI systems were adequate for diagnosis of challenging dermatopathology cases; our results agree with those findings. The feedback from the participating dermatopathologists in our study was entirely positive regarding image quality; their only concern was with speed of diagnosis in a subspecialty known for large workloads.…”
Section: Commentsupporting
confidence: 82%
See 1 more Smart Citation
“…Massone et al 20 reported, in 2007, significant problems with a WSI system for inflammatory cases; they noted that further system and technology development and additional training might improve accuracy. In 2012, Al Habeeb et al 15 reported concordance rates of 96% (76 of 79) and 100% (12 of 12) in a multiple-armed study, and they concluded modern WSI systems were adequate for diagnosis of challenging dermatopathology cases; our results agree with those findings. The feedback from the participating dermatopathologists in our study was entirely positive regarding image quality; their only concern was with speed of diagnosis in a subspecialty known for large workloads.…”
Section: Commentsupporting
confidence: 82%
“…Other possible explanations for that result include changes related to practice behavior, such as spending more time on the WSI, novelty-induced interest, or, potentially, viewing cases at higher magnifications. Studies of nonconsult-grade cases among multiple subspecialties, [7][8][9]13,14 and consult-grade cases among a single subspecialty 3,15,16 have been published previously. The only other study 12 that addresses consult-grade cases of multiple subspecialties, to our knowledge, showed a 91% agreement rate (48 of 53) between WSI and GS interpretation for a population of cases selected for difficulty from an outside institution.…”
Section: Commentmentioning
confidence: 99%
“…Given the limitations of the videoconferencing equipment, a thorough physical exam cannot be completed. Some studies have validated the use of videoconferencing by demonstrating high rates of concordance between diagnoses given after remote and face-to-face consultations [12][13][14]. However, these studies do not take into account the varying levels of health education and communication ability of patients who need humanitarian services.…”
Section: Potential Concerns About Telehealthmentioning
confidence: 99%
“…Although both studies included a small number of cases (100 and 79, respectively), the intraobserver agreement was high (94% for WSI and 96% for CLM, respectively) [30,56]. A study limited to tumor and tumor-like skin lesions showed agreement in the diagnosis by WSI and CLM, with a κ value of 0.93 for both methods [57].…”
Section: Dermatopathologymentioning
confidence: 99%